THE EFFECTIVENESS OF SPECIAL EXERCISES IN DEVELOPING ENDURANCE IN YOUNG FOOTBALL PLAYERS - Bori Nigmanov; Ramziddin Shodibekov (Bright Mind Publishing, 2025)
This article explores the effectiveness of special exercises in developing endurance in young football players. Emphasis is placed on the importance of endurance as a key physical quality that underpins overall performance in football. The study analyzes how age-appropriate and systematically organized exercises can improve cardiovascular capacity, muscular stamina, and recovery rates among youth athletes. Through a pedagogical and physiological lens, the paper examines the structure, intensity, and progression of endurance-oriented drills used during training. The article also evaluates the relationship between endurance development and the long-term athletic growth of young players. Findings indicate that properly selected and applied special exercises significantly contribute to enhancing endurance, ultimately improving the players’ match performance and resilience on the field.
Keywords: Endurance, youth football players, physical training, special exercises, sports performance, training methodology, athletic development.